Radical scavenging capacity of RuBisCO bioactive peptides derived from Dunaliella salina and Spirulina platensis: An in silico and in vitro study - Seyedeh Fahimeh Razavi; Leila Zarandi Miandoab; Elaheh Zadeh Hosseingholi; Nader Chaparzadeh (AIMS Molecular Science)
Microalgae have a large high-quality protein content that can be used as human protein supplements. Dunaliella salina and Spirulina platensis have been identified as rich sources of natural bioactive compounds. We aimed to examine the antioxidant properties of bioactive peptides using the enzymatic digestion of the ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) enzyme derived from D. salina and S. platensis microalgae. This was an in vitro and in silico study. Cell walls of D. salina and S. platensis were lysed, proteins were isolated, and RuBisCO fraction was concentrated. Then, the protein was enzymatically digested using pepsin, trypsin, and chymotrypsin. Finally, antioxidant activity was assessed at different stages (pre- and post-digestion). The 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay was used to assess the antioxidant potential of hydrolyzates both before and after digestion. Findings indicated that digestion over time, particularly by chymotrypsin, produced bioactive fragments with enhanced antioxidant properties. For the 0–35 protein fraction (which likely includes RuBisCO), the antioxidant potential of peptides derived from S. platensis was significantly greater than that from D. salina. We showed that chymotrypsin may be an appropriate enzyme to yield the highest peptide concentrations from the protein extracts of these microalgae with the highest antioxidant activity. Moreover, the results of digesting the RuBisCO sequence with digestive enzymes showed that antioxidant properties increased with the production of hidden bioactive peptides. This finding may lead to the application of RuBisCO protein and its derivative peptides in the food and pharmaceutical industries of S. platensis and D. salina.